Utilización del software libre linux Ubuntu como recurso didáctico activo en el proceso enseñanza-aprendizaje de las estudiantes del 10mo. año de educación básica del Colegio Técnico Femenino Dr. Camilo Gallegos Domínguez del cantón Arenillas, período lectivo 2012-2013. - Zhingre Padilla, Patricia Jackeline (2013)
Currently the use of free software is not very popular, although it is known that it is a software without license cost, as is also a Ministerial Decree, imposed by the current government, so it is important to delve a little deeper this matter.